Evaluation of cervical cytological abnormalities in correlation with clinical findings in Iraqi patients - Zainab Abbas Hassooni; Wafaa Redha Mohammed Al-Sabbagh; Taqi Mohammed Jwad Taher (Medical Journal of Babylon)
Abstract Objective: Many articles study the efficiency of pap smears in detecting cervical disease and precancerous lesions; however, in Iraq, only few researches study the clinic-pathological correlation in pap smear results. In this study, we will highlight the correlation of pap smears with the most important and frequent clinical data and findings on cervical examination. Materials and Methods: One hundred and twenty cases are collected from private clinics of gynecology in Al-Kut province during the interval (June 1, 2020, to February 28, 2021). Clinical history was obtained and pap smear test was examined by two pathologists. Data were analyzed using SPSS software program version 26. Results: There were significant statistical association between cytological abnormalities on pap smear test and age of the patient (P-value of 0.01), with low grade squamous intraepithelial lesion (LSIL) result showed the highest mean age of 46.91 as well as significant association with a number of live birth and a number of pregnancies with significant P value (<0.001 and <0.001) in the same order. Atypical squamous cells of undetermined significance were the most common cytological abnormality. Conclusion: Women should not delay their first screening pap test for more than 30 years of age since the mean age for LSIL (the most significant abnormality present in this study) was the age of 46. 91 ± 10.75. awareness about screening for cervical precancerous lesions should be increased especially among multiparous women and those more than 40 years of age.